Anti-Herpes Simplex Virus Type 1 Activity of Specially Selected Groups of Tannins - Vilhelmova-Ilieva, Neli; Jacquet, Rémi; Deffieux, Denis; Pouységu, Laurent; Sylla, Tahiri; Chassaing, Stefan; Nikolova, Ivanka; Quideau, Stéphane; Galabov, Angel S. (Drug Research, 2019)
Anti-herpes simplex virus (HSV-1) activity of 9 ellagitannins, including 6 natural compounds (castalin, vescalin, acutissimin A, epiacutissimins A and B, mongolicain) and 3 vescalagin synthetic derivatives (VgSBuSH, VgSOctSH, VgOMe), and 13 gallotannin-type compounds [Gal-01A, Gal-01B, Gal-02A, Gal-02B, Gal-03M, Gal-04A, Gal-04B, Gal-05M, Gal-07, Gal-08, Gal-09, Gal-11M (tannic acid), as well as Gal-12 (gallic acid), Gal-13 and Gal-14 (ellagic acid)] were examined in MDBK monolayer cell culture. Their antiviral activity was determined by the cytopathic effect (CPE) inhibition test and their cytotoxicity was evaluated through the neutral red uptake assay. In general, the series of ellagitannins showed a significantly stronger activity against HSV-1 replication than that of the gallotannins. Six of the tested ellagitannins manifested a well-pronounced activity: epiacutissimin B (selectivity index, SI>60.6), epiacutissimin A (SI>55.5), acutissimin A (SI>34.8), mongolicain (SI>32.5), VgSBuSH (SI>24.6) and VgOMe (SI>22.0). Four gallotannin-type compounds inhibited the replication of HSV-1 at a lower but still significant extent: Gal-04B (SI>35.7), Gal-04A (SI>28.5), Gal-11M (tannic acid) (SI>25) and Gal-05M (SI=15.6).
Keywords: ellagitannins; gallotannins; herpesvirus; antiviral screening in vitro